Evaluasi Rasio Netrofil Limfosit (RNL) untuk diagnosis COVID-19 pada Pasien di RS Tadjuddin Chalid, Makassar, Indonesia - Yenni Yusuf; Sitti Nurisyah; Ammar Abdurrahman Hasyim; Khaeriah Amru; Atifatul Qalbi Kadir; Azizah Nurul Mutia; Muhammad Naufal Zuhair; Kartika Paramita (Jurusan Biologi Universitas Negeri Makassar, 2021)
The neutrophil lymphocyte ratio (NLR) is one of the variables related to the severity of COVID-19 disease. Therefore, we evaluated the value of NLR in COVID-19 patients and its relation to the symptoms and severity of COVID-19 at Tadjuddin Chalid Hospital, Makassar. We recruited patients visiting Tadjuddin Chalid Hospital Makassar who were willing to take part in the study in April to August 2021. Demographic, clinical and laboratory data were recorded through interviews and medical records. The severity of the disease is classified according to the guidelines from the association of Indonesian pulmonary doctors, Indonesian internal medicine doctors, Indonesian pediatricians, anesthesiologists and intensive care doctors, and the Indonesian cardiologist association. NLR data was obtained by calculating the ratio between neutrophil levels and lymphocyte levels in the blood. A total of 130 patients took part in the study, between 19-72 years old. There were 77 subjects (59.2%) with mild symptoms, 28 (21.6%) with moderate symptoms, and 25 (19.2%) with severe symptoms. There were 89 subjects with NLR <3.5 (68.5%) and 41 (10.8%) with NLR > 3.5. NLR values in patients with severe and moderate disease were significantly different from NLR in patients with mild disease (p =0.0002 dan p<0.0001, respectively). However, no significant difference was found in NLR between patients who neither have cough nor fever with those who had one or both of those symptoms. The presence of clinical or radiological symptoms of pneumonia accompanied by an NLR > 3.5 can be used as an indicator for a suspected moderate or severe COVID-19 diagnosis.